2003
DOI: 10.1053/jlts.2003.50022
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolic acid pharmacokinetics in pediatric liver transplant recipients

Abstract: The aim of this study is to study mycophenolic acid (MPA) pharmacokinetics in stable pediatric liver transplant recipients and determine which times best represent the area under the concentration versus time curve (AUC) of MPA plasma concentrations. MPA pharmacokinetic profiles were determined in 21 liver transplant recipients (age, 2 to 15 years; 12 boys) administered mycophenolate mofetil (MMF) for at least 6 months. Ten patients were coadministered cyclosporine A (CsA), and 11 patients were coadministered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 28 publications
2
32
0
2
Order By: Relevance
“…In children after kidney or liver transplantation, in a few studies the significant correlation between MPA C trough and AUC 12 was proved (Filler, 2004;Aw et al, 2003). It was also observed that in children after renal transplantation, MPA C trough correlated well with the value of AUC 12 only in patients receiving steroids (Tönshoff et al, 2011).…”
Section: Discussionmentioning
confidence: 93%
“…In children after kidney or liver transplantation, in a few studies the significant correlation between MPA C trough and AUC 12 was proved (Filler, 2004;Aw et al, 2003). It was also observed that in children after renal transplantation, MPA C trough correlated well with the value of AUC 12 only in patients receiving steroids (Tönshoff et al, 2011).…”
Section: Discussionmentioning
confidence: 93%
“…Most data on MPA pharmacokinetics in liver transplant recipients consist in the determination of either predose MPA concentration as the only parameter assessed (6,7,9) or MPA AUC measured only once at variable periods following transplantation (7,8). There is only one investigation in which MPA pharmacokinetic parameters were determined sequentially during the early postoperative period (from one to six weeks after liver transplantation) (10), although no specific information was given in the study on whether fixed or changing doses of MMF were administered.…”
mentioning
confidence: 99%
“…Los efectos secundarios más frecuentes del MPA son las molestias gastrointestinales, entre las que predominan la diarrea, la leucopenia y, en menor grado, la trombopenia y anemia. Es posible que la monitorización en sangre del MPA pueda limitar los efectos secundarios del fármaco, aunque este hecho está por demostrar en estudios más amplios 19 . El MMF disminuye de forma significativa la incidencia de rechazo agudo tras el trasplante renal con respecto a la azatioprina 16,20 .…”
Section: Micofenolato Mofetil (Mmf): Papel En La Inmunodepresión Actuunclassified